(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
Nowadays, manufacturing industries demand lucrative, sustainable, and environment-friendly coolant materials to boost machining performance of difficult-to-cut materials. In machining process, the interaction of the tool with the workpiece generates higher temperatures, more friction, and consequently variation in its heat distribution. The metal shearing happens while machining and huge amount of mechanical energy is converted into heat energy due to the materialization of the chip. The most common method of boosting the machining efficiency of superalloys is the application of lubricants. It increases lifetime of tool and increase efficiency of machining methods. However, these methods may cause the ecological threats. Recently, scholars have proposed some methods alternative to conventional lubrication/cooling systems to support green manufacturing. Application of hybrid nano-lubricants handles the above problems as it delivers better permanence, heat transfer property, and greater surface-to-volume proportion without contaminating the atmosphere for machining superalloys. This research proposes a method for the synthesizing hybrid nano-lubricants by adding silica (SiO2) and Lanthania (La2O3) nano additives. This hybrid nano-lubricants is synthesized through the chemical wet synthesis technique without using powerful polar solvents. Variations in the crystalline configuration of Lanthania and deviations in surface features of binary oxides are studied for different composition of the Silica with Lanthania. Different samples of Si to La molar ratios of 0:1, 0.1:1, 0.2:1, 0.3:1, and 0.4:1 are analyzed through X-Ray Diffraction (XRD) examination. By evaluating the thermophysical characteristics of all the samples, this research chooses LaSi0.3 as the optimum specimen to synthesize nano-lubricants for machining superalloys. Then, the derived sample is dispersed in nitric acid (HNO3) to prepare Silica/Lanthania /Nitric acid lubricant.